Tagetes erecta L التأثير الفسيولوجي لرش معلق الخميرة الجافة في النمو لنبات الجعفري - محمد صالح السامرائي, سميرة; عثمان حسن, عبدالرزاق; نعيم حمد, يوسف (University of Thi-Qar Journal of Science, 2011)
This experiment was done on Tagetes erecta L .plant during the 2009 season to study the effect of yeast suspension with 1,2,3and4 g/L on vegetative and flowering growth , and product of beta-carotene pigments treatment with yeast suqension had significant increase ,for all vegetative growth ,the results of spraying with yeast suqension significantly increased the number of flowers and dry matter percentage for flowers with concentration 4g/L while concentration gave the greatest flowers diameter and beta-carotene –pigment but the high concentration 4g/L gave increase the percentage of Nitrogen ,Phosphorus and Potassium.